2023
DOI: 10.3390/geriatrics8010021
|View full text |Cite
|
Sign up to set email alerts
|

How Well Did the Healthcare System Respond to the Healthcare Needs of Older People with and without Dementia during the COVID-19 Pandemic? The Perception of Healthcare Providers and Older People from the SI4CARE Project in the ADRION Region

Abstract: One major challenge during the COVID-19 pandemic was the limited accessibility to healthcare facilities, especially for the older population. The aim of the current study was the exploration of the extent to which the healthcare systems responded to the healthcare needs of the older people with or without cognitive impairment and their caregivers in the Adrion/Ionian region. Data were collected through e-questionnaires regarding the adequacy of the healthcare system and were anonymously administered to older i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In our study, the face-to-face care of PLwD in their homes focused on the control of baseline pathologies, highlighting the leading role of the nurse, as well as their limitations and dependence on the doctor. In their study, Fragkiadaki et al (2023) argued that during the first wave of COVID-19, face-to-face medical visits were limited and even avoided, and telemedicine was proposed as an alternative, although it did not develop adequately. In our study, the use of telemedicine was via telephone, with no use of videoconferencing, most likely due to a lack of digital literacy among caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the face-to-face care of PLwD in their homes focused on the control of baseline pathologies, highlighting the leading role of the nurse, as well as their limitations and dependence on the doctor. In their study, Fragkiadaki et al (2023) argued that during the first wave of COVID-19, face-to-face medical visits were limited and even avoided, and telemedicine was proposed as an alternative, although it did not develop adequately. In our study, the use of telemedicine was via telephone, with no use of videoconferencing, most likely due to a lack of digital literacy among caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects the brain, primarily causing problems with memory, thinking, and behavior. AD is the most common cause of dementia, a general term for a decline in cognitive abilities severe enough to interfere with daily life [1,2]. The pathogenesis of AD is related to be a complex interplay of genetic, environmental, and lifestyle factors [3].…”
Section: Introductionmentioning
confidence: 99%
“…While there is currently no cure for AD and PD, various treatments and interventions can help manage symptoms and improve the quality of life for individuals with the condition [2]. These may include medication to temporarily improve cognitive function or manage behavioral symptoms and non-drug approaches such as cognitive stimulation, physical exercise, and support from caregivers [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine, referring to remote diagnosis and treatment through information and communications technology (ICT), represents a useful tool for bridging this widening gap [ 4 ]. During the COVID-19 pandemic, the need for remote healthcare was further emphasized, particularly for vulnerable individuals with chronic disorders, including those with neurodegenerative diseases [ 2 , 5 ]. Several studies have demonstrated that neurological and neuropsychological assessments via videoconferencing are reliable for cognitive and movement disorders compared to in-person evaluation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to investigate for the first time the perceptions of patients with cognitive and movement disorders, their caregivers, and healthcare professionals in the Aegean Islands of Greece toward the use of a specialized telemedicine service provided by an academic center during a 2-year period. This pilot study is part of the European Project SI4CARE (Social Innovation for integrated health CARE of ageing population in ADRION Regions), which aims to enhance cooperation among healthcare services for the effective application of social innovation in the health and social care of the elderly in the Adriatic-Ionian area [ 5 ].…”
Section: Introductionmentioning
confidence: 99%